1998
DOI: 10.1186/1297-9686-30-1-79
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal localization and activity of nucleolar organizer regions in the dog (Canis familiaris)

Abstract: Using fluorescent in situ hybridization on Q-banded chromosomes, nucleolar organizer regions (NORs) were localized on canine chromosomes 7qter, 17qter, Yqter and also terminally on a small autosome, not yet included in the dog standard karyotype. The analysis of NOR activity was carried out on Ag-I stained metaphases originating from 27 individuals (10 males and 17 females). The mean number of silver stained NORs was 6.0 in males and 5.3 in females and the modal number was 7 and 6, respectively. Interindividua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In humans, it can vary from 5 to 10, with clear individual, breed and population differences (9). Experiments with dogs showed that in the canine genome NORs are most often active on chromosome pairs 8,7,6,9,12, and 10 (the order is based on the degree of transcriptional activity), and least often on pairs 5 and 11 (25). Similar individual differences in the number of rDNA in NOR chromosomes were also observed in pigs (23), mice (33), rats (3), the Cavidae family (11), cattle (30), the Cervidae family (10), and horses (40).…”
Section: Tab 3 Mean and Standard Deviations (Sd) Of Silver Depositsmentioning
confidence: 99%
“…In humans, it can vary from 5 to 10, with clear individual, breed and population differences (9). Experiments with dogs showed that in the canine genome NORs are most often active on chromosome pairs 8,7,6,9,12, and 10 (the order is based on the degree of transcriptional activity), and least often on pairs 5 and 11 (25). Similar individual differences in the number of rDNA in NOR chromosomes were also observed in pigs (23), mice (33), rats (3), the Cavidae family (11), cattle (30), the Cervidae family (10), and horses (40).…”
Section: Tab 3 Mean and Standard Deviations (Sd) Of Silver Depositsmentioning
confidence: 99%
“…The following chromosome pairs of these species bear the NORs: 1, 4, 13 and Y in the Chinese raccoon dog (PIENKOWSKA and ZAGALSKA 2001) and 11, 12, 18 and Y in the Japanese raccoon dog (WARD et al 1987). The NORs in the canine karyotype were detected on two large autosomes (7 and 17), one small autosome and on the Y chromosome (MÄKINEN et al 1997;PIENKOWSKA and SWITONSKI 1998). The presence of the NOR on the Y chromosome reflects the evolutionary similarity of this chromosome in the dog and raccoon dog.…”
Section: Nucleolar Organiser Regions and Variability Of Their Activitymentioning
confidence: 99%
“…Kopp et al, 1982;Howard-Peebles et al, 1983;Mayr et al, 1986) provided inconsistent results about the number and the chromosomal localization of NORs. Recent publications by Mäkinen et al (1997) and Pienkowska and Switonski (1998) both identified three autosome pairs and the Y chromosome carrying the gene cluster for major rRNA genes using FISH and FISH/silver staining, respectively. Besides canine chromosome 7 and 17, a third autosome bearing the locus belonged to the group of small chromosomes (CFA 22-38), which were not yet included in the international standard karyotype.…”
mentioning
confidence: 99%